UPAYA PENINGKATAN EFISIENSI TEKNIS PRODUKSI TANAMAN PADI DESA NGADILUHUR KECAMATAN BALEN KABUPATEN BOJONEGORO (PENDEKATAN STOCHASTIC FRONTIER) - Nurkomariyah; Syafrial; Suhartini (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
The primary goal of this study was to explore and analyze the factors impacting the production and efficiency of wetland rice cultivation. Data collection occurred between December 2023 and January 2024 in the Balen District of Bojonegoro Regency. A sample of 60 farmers was randomly chosen for the study. Data analysis was conducted using the Stochastic Frontier Cobb-Douglas Production Function with the Frontier 4.1c software employing Maximum Likelihood Estimation (MLE). The study findings revealed that variables such as land size, NPK and organic fertilizers, labor, planting season, and pesticides all positively influenced wetland rice production, while seed quantity had a negative impact. All variables, except pesticides, exhibited significant effects at confidence levels above 10 percent. The technical efficiency of farmers in the research area was determined to be satisfactory, with an average technical efficiency (TE) of 75 percent, ranging from 43 percent to 95 percent. Educational outreach and guidance were identified as factors capable of reducing technical inefficiency or enhancing farming efficiency. Although factors like land ownership status and experience were associated with increased inefficiency, their statistical significance was minimal, with only land ownership significantly affecting technical inefficiency.